Filtration efficiency following polymer addition - Fabrizi, Lara (Cranfield University, 2007)
Natural organic matter has become an increasing concern in drinking water treatment, because of the potentially carcinogenic disinfection by-products that form when disinfectants react with the residual organic carbon not removed by the treatment process. Organic and inorganic matter at water treatment works (WTW s) is usually removed by aggregating the matter into large insoluble aggregates, known as floes, and then separating the floes from the water: Synthetic organic polymers are widely used to improve the characteristics of floes. These polymeric additions enhance natural organic matter removal in the subsequent separation phase. The efficiency of the reaction between polymer and floes is dependant on several factors such as the properties of the polymer and the particular site conditions. The choice of on-site polymer dosing is not simple because of the complex interactions between polymers and particulates, the influence of water quality and. operating conditions. Polymer dosing in drinking water treatment does not follow a general rule and is usually based on trial and error or industrial experience. This thesis details the work conducted to provid~ diagnostic support to existing onsite investigation on the optimum polymer dose and conditions required for the treatment of natural organic matter rich waters at Albert WTWs, Yorkshire, UK. Seasonal variations in water quality were investigated both at the iaboratory scale and full-scale. The effect of polymer dosing on floe filterability was studied on water samples collected at Albert WTWs using a jar tester and two particle sizing instruments based on laser diffraction. Outlet turbidity and headloss were monitored during laboratory sand filtration experiments. The results of the on-site data analysis showed great variability in the effect of site conditions on sand filtration performance. Polymer dosing as a filter aid improved particle removal by sand filtration during winter, that resulted in lower filtered turbidity and ultraviolet light at 254 nm wavelength. The results of laboratory experiments demonstrated that polymer dosing increased floe size and re-growth and marginally improved floe strength, particularly for waters at low dissolved organic carbon content. Temperature had no significant impact on floe size or strength. The bench scale filter trials showed that there was an increase in the filter headloss with increasing polymer dose. Outlet turbidity was higher when no polymer was dosed and this was explained by performing particle count analysis on the inlet and the outlet of the bench sand filter. The results showed that when no polymer was dosed the filtrate contained a higher number of particles than when polymer was dosed. The number of particles in the inlet water decreased proportionally .to the amount of polymer dosed, particularly after floe growth. Polymer dosing has the effect of mopping up small particles and so makes them easier to filter. Polymer dosing engineers floe characteristics for improved filtration by reducing the concentration of particles onto the sand filters. The optimum dose of synthetic polyacrylamide on water after dissolved air flotation at Albert water treatment works is between 0.01 and 0.02 mg/L: such a dose ensures long filter runs and low outlet turbidity.